PENGARUH MOTIVASI DAN KEPEMIMPINAN PARTISIPATIF TERHADAP KINERJA KARYAWAN PADA RUMAH MAKAN AYAM BAKAR WONGSOLO CABANG BANJARMASIN - Dewi Ariefahnoor (At-Tadbir : jurnal ilmiah manajemen, 2017)
The development of restaurant business nowadays has shown a positive trend. This provides an opportunity for restaurant owners to raise the level of sales. This study aims to determine the effect of motivation and participative leadership on the performance of employees at Ayam Bakar Wong Solo Restaurant Banjarmasin either partially or simultaneously. Sampling technique in this research using probability sampling technique. The number of samples involved in this study are 30 customers. Instruments in this study is questionnaires and observations. All data were analyzed using multiple regression analysis technique. The result of hypothesis test proves that motivation variable have positive and significant effect to employee performance variable with influence magnitude 0,481. And participative leadership has a positive and significant effect on employee performance with the magnitude of influence of 0.270. In addition, motivation and participative leadership variables simultaneously have a positive and significant effect on employee performance with the influence magnitude of 0.808.Keyword: Motivation, Participative Leadership, Employee Performance